Equine rotavirus in Argentinean foals : an overview - Parreño, Viviana; Miño, Samuel; Garaicoechea, Lorena Laura; Barrandeguy, Maria Edith (2017)
The aim of the present work is to summarized our knowledge and discuss the future prospects regarding this important disease of foals.